Emotional Socialization and Emotional Intelligence Prevent Aggressive Behavior among School-age Children in the Rural Family - Alfiasari Alfiasari; Meilia Rachmawati (Journal of Child Development Studies, 2017)
Emotional socialization is important factor to shape emotional intelligence for children. Children who have high emotional intelligence will prevent to behave aggressively. Basic emotions in children such as anger, sadness, and fear is still regarded as inappropriate emotions expressed. The aimed of this research was to analyze the effect of emotional socialization of three basic emotions and emotional intelligence on aggressive behavior of school-age children in the rural family. This research was conducted at Ciasmara and Ciasihan Village, Pamijahan Sub District, Bogor Regency. Design of this research was cross sectional. The samples of this research were intact family who had school-aged children. Hundreds students were selected by proportional random sampling in the two selected school. Result showed that there were significant positive correlation between emotional socialization and emotional intelligence. Emotional intelligence was significant negatively correlated with aggressive behavior. Other result found that mother’s age, acceptance dimension of emotional socialization, awareness and self-regulation of emotional intelligence had significant influences on aggressive behavior among school-age children of rural family